GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 2553 species occurrences available in GBIF matching the query: TaxonKey: Casuariidae. The dataset includes 2553 records from 89 constituent datasets: 1 records from DMNH Eggs. 7 records from University of Ghent - Zoology Museum - Vertebratacollectie. 2 records from OEH Atlas of NSW Wildlife. 79 records from Australian National Wildlife Collection provider for OZCAM. 18 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 12 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 1 records from Zoology (Museum of Evolution - Uppsala). 7 records from KUBI Ornithology Tissue Collection. 2 records from UAFMC Birds. 2 records from DMNS Bird Collection (Arctos). 1 records from ISM Ornithology Collection. 17 records from Field Museum of Natural History (Zoology) Bird Collection. 46 records from Museum Victoria provider for OZCAM. 5 records from Eggs Specimen. 4 records from Lund Museum of Zoology (MZLU). 3 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 145 records from Historical Bird Atlas. 219 records from BirdLife Australia, Birdata. 10 records from Museum of Comparative Zoology, Harvard University. 8 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 6 records from CAS Ornithology (ORN). 641 records from EOD - eBird Observation Dataset. 2 records from Tasmanian Museum and Art Gallery provider for OZCAM. 10 records from iNaturalist Research-grade Observations. 3 records from NYSM Birds. 3 records from Birds collection of Yamashina Institute for Ornithology. 3 records from University of California Museum of Paleontology. 35 records from NMNH occurrence DwC-A. 1 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 2 records from naturgucker. 14 records from UMZC Zoological Specimens. 2 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 3 records from Bird Specimens in the Museum of Nature and Human Activities, Hyogo, Japan. 140 records from First Bird Atlas. 3 records from SBMNH Vertebrate Zoology. 8 records from LACM Vertebrate Collection. 5 records from Collection Ornithologie - ZSRO. 4 records from Western Australian Museum provider for OZCAM. 432 records from Natural History Museum (London) Collection Specimens. 9 records from Macaulay Library Audio and Video Collection. 34 records from RBINS collections. 15 records from Collection Anatomie Histologie - SMF. 1 records from Estacion Biologica Donana - CSIC, Aves. 2 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AVES. 1 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 1 records from Paleobiology Database. 7 records from LSUMZ Birds Collection. 9 records from Individual Sightings. 5 records from Birds Specimens. 5 records from SDNHM Birds Collection. 4 records from Database Schema for UC Davis Wildlife museum. 2 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 2 records from MMNH Museum Bird Collection. 20 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 1 records from UCLA Donald R. Dickey Bird and Mammal Collection. 8 records from ORN. 3 records from Aves MZS. 142 records from Naturalis Biodiversity Center (NL) - Aves. 18 records from WFVZ Bird Collections. 1 records from Natural History Museum, University of Tartu. 2 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 1 records from New Mexico Biodiversity Collections Consortium database. 1 records from Bird specimen detabase of Kanagawa Prefectural Museum of Natural History. 1 records from Biological and palaeontological collection and observation data MNHNL. 14 records from Collection Aves (spirit preserved) SMF. 20 records from Collection Aves (bird skeletons) SMF. 35 records from Collection Aves (bird skins) SMF. 55 records from AMNH Bird Collection. 4 records from MVZ Egg and Nest Collection (Arctos). 1 records from Colección Nacional de Ornitología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1 records from Bird Specimens. 46 records from Queensland Museum provider for OZCAM. 2 records from CM Birds Collection. 9 records from Auckland Museum Land Vertebrates Collection. 8 records from Animal Sound Archive. 13 records from Bernice P. Bishop Museum. 27 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Cowan Tetrapod Collection - Birds. 2 records from UTEP Vertebrates. 3 records from UMMZ Birds Collection. 2 records from MSB Bird Collection (Arctos). 32 records from Australian Museum provider for OZCAM. 11 records from MVZ Bird Collection (Arctos). 6 records from KUBI Ornithology Collection. 11 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 7 records from CUMV Bird Collection (Arctos). 34 records from South Australian Museum Australia provider for OZCAM. 6 records from LSUMZ Bird Tissues. 2 records from Bird Collection of Museum and Institute of Zoology PAS.
Keywords: GBIF; biodiversity; species occurrences